2017
DOI: 10.4081/ija.2017.773
|View full text |Cite
|
Sign up to set email alerts
|

Probing the responses of four chicory ecotypes by ethylene accumulation and growth characteristics under drought stress

Abstract: Water deficit is the largest limiting abiotic factor in agriculture and will increase in future. Evaluating the drought stress-induced changes in growth parameters as well as the leaves ethylene accumulation of medicinal plants to grow these in arid and semi-arid areas has particular importance. Chicory (Cichorium intybus L.) is a famous medicinal herbal plant which grows in most parts of Iran. A factorial greenhouse experiment was conducted to evaluate the effect of drought stress [100 (as a control), 80, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Conversely, C. intybus and T. officinale were the least interesting products, not suitable for storage using the described experimental conditions, as the first one rapidly went rotten and the second one was suitable only on the day of harvest. There is evidence that these two species release ethylene [109,110], the hormone that affects the growth, development, and storage of many vegetables, fruits, and ornamental plants [111].…”
Section: Shelf Lifementioning
confidence: 99%
“…Conversely, C. intybus and T. officinale were the least interesting products, not suitable for storage using the described experimental conditions, as the first one rapidly went rotten and the second one was suitable only on the day of harvest. There is evidence that these two species release ethylene [109,110], the hormone that affects the growth, development, and storage of many vegetables, fruits, and ornamental plants [111].…”
Section: Shelf Lifementioning
confidence: 99%
“…Stress conditions can induce high levels of ethylene in plants and halt root elongation and nitrogen fixation [ 21 ]. Sadeghi et al [ 285 ] found that water deficiency led to ethylene accumulation in leaves, lowering the biomass, leaf area and plant height of the medicinal herb Cichorium intybus . 1-aminocyclopropane-1-carboxylate (ACC) is the vital precursor for ethylene synthesis.…”
Section: Function Of Soil Microorganisms In Growth Promotion and Qual...mentioning
confidence: 99%